2010
DOI: 10.1177/0960327110389926
|View full text |Cite
|
Sign up to set email alerts
|

Gender-related difference in liver injury induced by Dioscorea bulbifera L. rhizome in mice

Abstract: The present study was undertaken to investigate the gender-related liver injury induced by Dioscorea bulbifera L. (DB), a traditional medicinal plant, in mice, and further explored its hepatotoxic chemical compound. Serum and liver tissue samples were collected at 0, 4, 8, 12 h, after mice were administrated orally with 640 mg/kg ethyl acetate extracts (EF) isolated from DB. After treatments, serum alanine transaminase (ALT) and aspartate transaminase (AST) activities were both significantly elevated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
69
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 44 publications
4
69
1
Order By: Relevance
“…There are increasing evidences that oxidative stress plays a critical role in liver diseases [23][24][25] . Harmful stimulation induces the excessive generation of reactive oxygen species (ROS) in liver.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are increasing evidences that oxidative stress plays a critical role in liver diseases [23][24][25] . Harmful stimulation induces the excessive generation of reactive oxygen species (ROS) in liver.…”
Section: ■ Discussionmentioning
confidence: 99%
“…cisplatin (40 mg/kg, dissolved in 0.9% normal saline) only once on the sixth day. The mice in groups 3,4 were served as hyperin (25,50 mg/ kg) + cisplatin groups, which were administrated intragastrically (i.g.) hyperin (25, 50 mg/kg per day) for six consecutive days, and one hour after the final administration of hyperin, cisplatin was injected intraperitoneally.…”
mentioning
confidence: 99%
“…Recently, study of the hepatotoxicity of D. bulbifera has attracted great interest. Our previous studies have already showed that an ethyl acetate extract (EF) isolated from D. bulbifera could induce oxidative stress liver injury (3,4). Meanwhile, our studies and other reports found that diterpenoids were the main hepatotoxic compounds in D. bulbifera, such as diosbulbin B and diosbulbin D (3,5).…”
Section: Introductionmentioning
confidence: 95%
“…The cellular anti-oxidant system in the body prevents ROS-induced cell injury; the system includes low-molecular-mass anti-oxidants (van der Vliet et al, 1999) such as glutathione, α-tocopherol, ascorbic acid, and the main anti-oxidant enzymes including copper-and zinccontaining superoxide dismutase (CuZn-SOD) and catalase (CAT). Our previous report demonstrated that oxidative stress plays an important role in liver injury induced by acetate extracts of D. bulbifera (Wang et al, 2011); however, whether the protection by ferulic acid against liver injury induced by diosbulbin B is related to the liver anti-oxidant system has not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in northern Bangladesh, it is used to treat tumors and leprosy (Murray et al, 1984). Our laboratory studies have shown that D. bulbifera rhizome can induce hepatotoxicity (Wang et al, 2010;2011), which emphasizes a potential toxicity in the clinical setting. Among the biologically active substances in D. bulbifera rhizome, a major class is the clerodane diterpenoids (Wang et al, 2009;Liu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%